2017
DOI: 10.1016/j.proci.2016.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygenation in cyclic hydrocarbons on chain-termination reactions from R + O2: tetrahydropyran and cyclohexane

Abstract: Multiplexed photoionization mass spectrometry (MPIMS) is used to determine branching fractions of conjugate alkenes from R + O 2 oxidation reactions for cyclohexane ( c -C 6 H 12 ) and tetrahydropyran ( c -C 5 H 10 O), a lignocellulosic-derived oxygenated biofuel. Because conjugate alkene formation is coincident with the formation of HO 2 , the results reveal the temperature-and pressure-dependent influence of the oxygen heteroatom on chain-termination propensity. The experiments were conducted using Cl-initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 25 publications
5
43
0
Order By: Relevance
“…This value is similar to those reported for alkyl radicals including pentyl radicals [31,32]. However, recent studies [1,33] revealed…”
Section: C-h Bond Dissociation Energysupporting
confidence: 90%
See 1 more Smart Citation
“…This value is similar to those reported for alkyl radicals including pentyl radicals [31,32]. However, recent studies [1,33] revealed…”
Section: C-h Bond Dissociation Energysupporting
confidence: 90%
“…The formation of the 2-hydroxy-4-penten-1-yl radical (C5H8OH2D-A) from the 3-hydroxycyclopentyl radical has the lowest energy barrier, while the highest-energy is estimated for the reaction with the same reactant but forming the 1-hydroxy-4-penten-1-yl radical(C5H8OH1-4). These values are on a similar level as that for the cyclopentyl radical[30] and are much higher than those for tetrahydrofuranyl molecules[1,33]. The ring-opening reactions of hydroxycyclopentyl radicals are expected to take place only at intermediate and high temperatures.…”
mentioning
confidence: 55%
“…One type of biofuels is lignocellulosic biofuels, mainly contains cellulose, hemicellulose, and lignin. 20 Cellulose is composed of glucopyranose (in the form of a (C6H10O5)n polymer), and hemicellulose of C5/C6 polysaccharides, Tetrahydropyran (THP) and tetrahydrofuran (THF) is the base structure of monosaccharides of hemicellulose, and themselves are a lignocellulosic-derived biofuels. 21 The utilization of biofuels, lignocellulosic derived, is most practical in blends with conventional fuels and integration as blending components require fundamental insight into the underlying autoignition chemistry.…”
Section: List Of Tablesmentioning
confidence: 99%
“…142 and THP has been studied in combined experimental and computational investigations. 20,[143][144] Mass spectra and photoionization efficiency spectra of many intermediates and products in THF 143 and THP 20…”
Section: Global Fittingmentioning
confidence: 99%
See 1 more Smart Citation